2017
DOI: 10.3329/ptcb.v27i2.35025
|View full text |Cite
|
Sign up to set email alerts
|

RAPD Profile Analysis of Single and Multigrain Aman Rice (Oryza sativa L.) Varieties Available in Bangladesh

Abstract: Genetic variation in 14 local Aman rice varieties of Bangladesh including single grain and multigrain rice was investigated at the DNA level by RAPD molecular typing. Fifteen random primers were initially screened against DNA from five individuals that generated highly reproducible RAPD fragments, which were then subjected to further population analysis. A total 191 RAPD fragments were generated with these primers and 153 (80.1%) were polymorphic, which indicated high level of polymorphism existed within these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…1). Mitra et al (2017) reported the lowest genetic distance between two multi-grain cultivars, Biram sundari and Double rice, which indicates close relations within multi-grain varieties. Guarino (2012) found that the clustered spikelets may be borne directly on the long primary branches of the panicle or on short secondary branches in varying proportions.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…1). Mitra et al (2017) reported the lowest genetic distance between two multi-grain cultivars, Biram sundari and Double rice, which indicates close relations within multi-grain varieties. Guarino (2012) found that the clustered spikelets may be borne directly on the long primary branches of the panicle or on short secondary branches in varying proportions.…”
Section: Resultsmentioning
confidence: 92%
“…2.5 -3.0 t/ha and suitable for cultivation in both Aman and Boro seasons (Anon. 2012, Mitra et al 2017. It can be used as a potential genetic resource for further breeding programme to ensure the food security in future (Ren et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biram sundari, a double grained rice cultivar with a grain yield of 2.5 -3.0 t ha -1 was reported from Birampur Upazila of Dinajpur district in Bangladesh, previously (Anon., 2012; Mitra et al, 2017). The multiple pistils are responsible for multiple grains within a single rice spikelet which is a very rare and unique feature in rice morphology (Sarwar and Chanda, 2018).…”
Section: Introductionmentioning
confidence: 99%